2009
DOI: 10.1016/j.micpath.2008.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Brief heat treatment increases cytotoxicity of Mannheimia haemolytica leukotoxin in an LFA-1 independent manner

Abstract: Mannheimia haemolytica is an important respiratory pathogen in cattle. Its predominant virulence factor is a leukotoxin (LKT) that is a member of the RTX family of exotoxins produced by a variety of gram negative bacteria. LKT binds to the CD18 chain of β2 integrins on bovine leukocytes, resulting in cell death. In this study, we show that brief heat treatment of native LKT (95 °C for 3 min) results in increased cytotoxicity for BL-3 (bovine lymphoblastoid) cells. Similar heat treatment restored the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The cytotoxicity of heat-activated HLY for this cell line ( Figure 2E) was similar to the previously reported results for heatactivated M. haemolytica LKT. (48) Interestingly, brief heat treatment also restored cytotoxicity to HLY that had been inactivated by incubation at room temperature for 3-5 days (white bars in Figure 2A-2D). Preincubation of heat-activated native HLY or inactive HLY with polyclonal anti-hemolysin antisera reduced the cytotoxicity effects of both heat-activated native HLY and inactive HLY (Figure 2A-2E).…”
Section: Brief Heat Treatment Of E Coli Hly Enhances Cytotoxicity Anmentioning
confidence: 90%
See 4 more Smart Citations
“…The cytotoxicity of heat-activated HLY for this cell line ( Figure 2E) was similar to the previously reported results for heatactivated M. haemolytica LKT. (48) Interestingly, brief heat treatment also restored cytotoxicity to HLY that had been inactivated by incubation at room temperature for 3-5 days (white bars in Figure 2A-2D). Preincubation of heat-activated native HLY or inactive HLY with polyclonal anti-hemolysin antisera reduced the cytotoxicity effects of both heat-activated native HLY and inactive HLY (Figure 2A-2E).…”
Section: Brief Heat Treatment Of E Coli Hly Enhances Cytotoxicity Anmentioning
confidence: 90%
“…(45,46) It is well recognized that heat treatment (>65°C) for 30-60 min eliminates the cytotoxicity of RTX toxins. (47) However, we recently demonstrated that a brief heat treatment of the M. haemolytica LKT resulted in greater cytotoxicity, (48) which was accompanied by an irreversible change in secondary structure as determined by circular dichroism (CD) spectroscopy. Varied biophysical approaches have identified other proteins (e.g.…”
Section: Original Articlementioning
confidence: 99%
See 3 more Smart Citations